2020
DOI: 10.36740/wlek202006110
|View full text |Cite
|
Sign up to set email alerts
|

Complex Estimation of Fitness Training Systems And Women’s Somatic Health of the First Period Mature Age

Abstract: The aim: To model, to ground and to check experimentally the efficiency of the complex organized system of fitness trainings and system of health improving trainings; to discover their influence on the status of women’s somatic health of the first period mature age. Materials and methods: Analysis, systematization, pedagogical observation, modelling, pedagogical experiment, tests: Ruffier, Stange, Romberg’s, Harvard step test and tests of PWC170. Results: Complex organized system of fitness trainings (dosed, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…Analysis of the scientific literature [4,5,8,20] confirmed that today a wide variety of health technologies encourages the invention of optimal fitness-technologies depending on age and individual characteristics, which was confirmed by our research.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Analysis of the scientific literature [4,5,8,20] confirmed that today a wide variety of health technologies encourages the invention of optimal fitness-technologies depending on age and individual characteristics, which was confirmed by our research.…”
Section: Discussionsupporting
confidence: 85%
“…It is known that under the influence of regular physical activity there is a number of positive changes in the body: metabolism improvement, activity of the cardiovascular and respiratory systems, increases the level of physical fitness, vitality and efficiency [4][5][6][7]. Regular exercise slows down the aging process of muscle tissue, helps maintain strength, flexibility and beauty of the body, improves body posture and locomotion, stabilizes blood pressure, heart rate, prevent the deposition of salts in the joints, help the body cope with overexertion and stress, as well as significantly improves general level of fitness [7][8].…”
Section: Introductionmentioning
confidence: 99%